Crack propagation in light alloys Ministry of Aviation contract no. PD/28/07 - Younger, A. (College of Aeronautics, 1965)
The revised approach to the measurement of the rate of crack propagation in light alloys has entailed the development of new experimental techniques, in particular the development of a multi-channel interval timer. The design of this instrument and descriptions of the new techniques are reported here together with the results of some preliminary evaluation tests.